CLINICAL AND LABORATORY PROFILE OF PATIENTS WITH HEPATITIS B INFECTION ATTENDING THE OUTPATIENT DEPARTMENT OF A TERTIARY CARE HOSPITAL IN NORTHEAST INDIA - RAM, RATAN; BEYONG, TASO (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: The objective of this study was to analyze the clinical and laboratory profile of patients with hepatitis B infection-attending outpatient departments of tertiary care hospitals in northeast India. Methods: This was a cross-sectional study conducted in the outpatient department of a tertiary care medical institute situated in northeast India. Eighty patients infected with hepatitis B (on the basis of serological markers) were included in this study on the basis of predefined inclusion and exclusion criteria. Demographic details such as age, gender, and socioeconomic status of all the patients were noted. A detailed history was taken including any history of intravenous drug use, tattooing, sexual contacts, history of blood transfusions, and familial liver disease. Clinical and laboratory profiles (liver function test and serological markers) of all the patients were studied. Ultrasound imaging was done in all the cases. p<0.05 was taken as statistically significant. Results: Out of 80 studied cases, there were 49 (61.25%) males and 31 (38.75%) females. The mean age for males and females was 32.30±8.03 and 34.70±13.52 years, respectively. There was no significant difference in mean age between males and females (p=0.3218). Mother-to-child transmission was evenly distributed with 7 males (8.75%) and 9 females (11.25%) affected. Other risk factors, such as dental implants and surgeries, showed a lower prevalence, with dental implants impacting 2 males (2.5%) and 3 females (3.75%) and surgeries concerning 5 males (6.25%) and 3 females (3.75%). Majority of the patients (52.5%) were asymptomatic and were found to be hepatitis B surface antigen (HBsAg) positive incidentally. HBsAg was positive in all cases. 12 (15%) patients showed the presence of hepatitis B e antigen suggestive of high infectivity. Anti-HBc and anti-HBe were positive in 68 (85%) patients each. Hepatomegaly was seen in 23 cases (28.75%) on ultrasound. Moderate fibrosis on elastography was seen in 2 (2.5%) cases. Conclusion: In cases of hepatitis B, the majority of the patients remained asymptomatic, and many cases no risk factor for hepatitis B virus infection could be identified. It is therefore important to screen the general population for hepatitis B infection.